Candida and dental caries in children, adolescents and adults: A systematic review and meta-analysis. (November 2020) - Eidt, Gustavo; Waltermann, Elen Darlise Marques; Hilgert, Juliana Balbinot; Arthur, Rodrigo Alex
Highlights: Ppresence of Candida spp.in oral cavity is associated with higher prevalence of caries. This association seems to be weaker for older individuals. Microbial cross-kingdom communities are important for caries development. Caries management strategies should consider the presence of Candida in oral cavity. Abstract: Objective: This systematic review and meta-analysis aimed to investigate whether the presence of fungi of the genus Candida in oral cavity is associated with dental caries in children and adolescents (from 6 to 18 years) or in adults (older than 18 years). Design: Electronic search was carried out in MEDLINE, EMBASE and LILACS databases. Studies that evaluated the presence of Candida spp. and dental caries on those individuals were included. Data extraction and evidence quality assessment were performed by two independent investigators. Prevalence ratio (PR) was calculated considering 95 % confidence interval (CI). Meta-analysis was performed using random effect Mantel-Haenszel model. Results: Thirty out of 123 publications selected for full-reading were included in the systematic review. Prevalence of Candida spp. in the oral cavity ranged from 7.7 % to 78 %. Prevalence of dental caries in individuals harbouring Candida spp. ranged from 27.2%–100% and was higher than in individuals not harbouring Candida spp. (PR = 1.72 [1.46–2.02]). Prevalence of dental caries was 2.3 times higher in individuals harbouring Candida spp. in mucosa. Moreover, dental caries prevalence was 80 % and 48 % higher in children/adolescents and adults harbouring Candida spp., respectively (95 % CI [1.44–2.25] and [1.20–1.83]). The quality of evidence of most studies (n = 21) was graded as fair. Conclusions: These results suggest that, regardless of age or sample site, individuals with the presence of Candida spp. have a higher prevalence of dental caries when compared to individuals without these microorganisms in the oral cavity.